The Impact of Revenue from Treasury Looting on The Economic Performance of Nigeria - Victor Chibuike EBERECHI; Ebele P. IFIONU; Godfrey O. OMOJEFE (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2024)
This study investigates the intricate relationship between revenue from treasury looting and economic performancein Nigeriafrom 1990 to 2021.The study employs secondary data which were gotten from various sources such as the Central Bank of Nigeria Statistical Bulletin and the Nigerian Bureau of Statistics. The findings of the study reveal several key insights. First, corruption through treasury lootingsignificantly negatively impacts Nigeria's economic growth. Higher perceived corruption levels are associated with lower GDPGR, highlighting the adverse effects of corruption on economic development.Second, the study identifies a positive short-term relationship between the growth rate of reported looted funds (TLFN) and GDPGR. However, this effect may not be sustainable in the long run, raising concerns about the sources and implications of such funds on the economy.The practical implications of these findings underscore the imperative of anti-corruption efforts in Nigeria. Strengthening governance, enhancing transparency, and implementing effective anti-corruption measures are essential for promoting sustainable economic growth. While short-term economic boosts from looted funds may occur, they are not a viable strategy for long-term development and can undermine trust in the economy.This study contributes to the ongoing discourse on corruption and economic performance in Nigeria and provides valuable insights for policymakers, stakeholders, and researchers. It emphasizes the need for sustained and comprehensive efforts to combat corruption and foster an environment conducive to economic prosperity in the country.